2020
DOI: 10.1016/j.jpainsymman.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Pain in Patients Undergoing Lung Cancer Surgery: A Longitudinal Prospective Study

Abstract: Context. Lung cancer surgery is among the surgical procedures associated with the highest prevalence of pain, but prospective longitudinal studies following the pain trajectory are scarce. Objectives. We aimed to describe the pain trajectory in patients undergoing surgery for primary lung cancer and to investigate whether distinct groups of patients could be identified based on different pain trajectories. Methods. Patients (n = 264, 95% thoracotomies) provided data on the average and worst pain intensity, pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…The year of publication of the included studies ranged from 2014-2020, including crosssectional studies (n= 2) (27,28), longitudinal cohort studies (n=8) (29)(30)(31)(32)(33)(34)(35)(36) and randomized controlled trials (n=2) (37,38) (see table 2). Eleven out of 12 included studies contained stage I-III cancer patients (27,28,38,(29)(30)(31)(32)(33)(34)36,37) and only one study contained stage I patients (35). This systematic review included 10 studies with breast cancer (27,28,(30)(31)(32)(33)(34)(36)(37)(38) and two studies with lung cancer patients (table 2) (29,35).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The year of publication of the included studies ranged from 2014-2020, including crosssectional studies (n= 2) (27,28), longitudinal cohort studies (n=8) (29)(30)(31)(32)(33)(34)(35)(36) and randomized controlled trials (n=2) (37,38) (see table 2). Eleven out of 12 included studies contained stage I-III cancer patients (27,28,38,(29)(30)(31)(32)(33)(34)36,37) and only one study contained stage I patients (35). This systematic review included 10 studies with breast cancer (27,28,(30)(31)(32)(33)(34)(36)(37)(38) and two studies with lung cancer patients (table 2) (29,35).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eleven out of 12 included studies contained stage I-III cancer patients (27,28,38,(29)(30)(31)(32)(33)(34)36,37) and only one study contained stage I patients (35). This systematic review included 10 studies with breast cancer (27,28,(30)(31)(32)(33)(34)(36)(37)(38) and two studies with lung cancer patients (table 2) (29,35). There were nine pain prevalence rates reported up to three months after surgery (27,29,32,35,37,38), one during chemotherapy (28), two up to three months after chemotherapy (30,33) and five pain prevalence rates up to three months after radiotherapy (table 2) (31,34,36,38).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative pain is the most prominent symptom that affects the quality of life of cancer patients [25][26][27]. Our results showed that the severity of pain after esophagectomy peaked on day 1 after surgery.…”
Section: High Incidence and Long Recovery Time Of Pain After Surgerymentioning
confidence: 66%
“…However, the patients say that they initially experience pain, fatigue and changes in their body and that this can make it difficult to meet their own and the health professionals' expectations. Oksholm et al (2015) have reported that, for example patients after lung cancer surgery may experience a high number of symptoms and also how especially pain may be highly prevalent (Gjeilo et al, 2020). Norlyk and Harder (2009, 2011) reach similar findings of the difficulty for patients to meet expectations in their studies on colon cancer patients in an ERAS programme.…”
Section: Discussionmentioning
confidence: 99%